2D animation as a Creative Learning Model in Art and Culture Education: A Study of Rizky Riplay's Works - Artanto, Aphief Tri; Sunarmi, Sunarmi; Handriyotopo, Handriyotopo (Yayasan Keluarga Guru Mandiri, 2026)
This study examines the dimensions of social criticism and creative character in his works, formulates learning principles derived from them, and offers a conceptual framework aligned with current digital education. This qualitative descriptive study is based on a research and development framework. Nine selected YouTube episodes and interviews with media and education experts were used as the main data sources. The analysis shows that Rizky Riplay's animated works not only combine humor, irony, and cultural fusion for entertainment, but also serve as a critical reflection of efforts to strengthen moral awareness. Based on these findings, six pedagogical principles were identified that emphasize contextual creativity, humor-based learning, visual literacy, participatory engagement, and ethical reflection. The findings of this study show that digital animation by local artists serves as a structured creative-critical educational model that is connected to cultural identity and educational innovation. Theoretically, this study broadens the understanding of creative learning and practically contributes to critical media literacy in the context of arts and cultural education. The findings of this study indicate that digital animation by local artists serves as a structured model of creative-critical education that is connected to cultural identity and educational innovation.